PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER TERHADAP HASIL BELAJAR PENGETAHUAN DASAR TEKNIK MESIN SISWA DI SMK NEGERI 1 MOTOLING - Riscky Roinal Balebu; Yohanis Rampo; Hendrik Sumaraw (Pendidikan Teknik Mesin, 2020)
Choosing the right learning model is something that the teacher needs to pay attention to to improve student learning outcomes in following the learning process in basic knowledge of mechanical engineering. This study aims to determine how activities, differences in learning outcomes and student responses after using the cooperative learning model type numbered head together (NHT). The type of research used is the pri experimental design with the pri test - post test design. The population and sample in this study were all students of class x SMK Negeri 1 Motoling, totaling 13 students. Data collection consisted of pre-test and post-test and documentation. Student learning outcomes data were analyzed using peired T test obtained tcount = 13.86 and ttable = 1.77 so that tcount ˃ ttable or 13.86 ˃ 1.77. Therefore H1 is accepted and H0 is rejected. From these results it can be concluded that the activities, learning outcomes and responses of students who apply the cooperative learning model type numbered head together (NHT) affect the results of learning basic knowledge of mechanical engineering.